2020
DOI: 10.1371/journal.pone.0230601
|View full text |Cite
|
Sign up to set email alerts
|

QTL mapping for quality traits using a high-density genetic map of wheat

Abstract: Protein-and starch-related quality traits, which are quantitatively inherited and significantly influenced by the environment, are critical determinants of the end-use quality of wheat. We constructed a high-density genetic map containing 10,739 loci (5,399 unique loci) using a set of 184 recombinant inbred lines (RILs) derived from a cross of 'Tainong 18 × Linmai 6' (TL-RILs). In this study, a quantitative trait loci (QTLs) analysis was used to examine the genetic control of grain protein content, sedimentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 48 publications
(33 reference statements)
3
30
0
Order By: Relevance
“…The QTL cluster of 3AS.1 colocalized with a detected QTL regulating grain protein content under late sowing time (LGPC) and wet gluten content under late sowing time (LWGC) reported by Lou et al (2020) . The QTL cluster of 3AL in this study overlapped with a detected QTL for LWGC and grain starch content under normal sowing time ( Lou et al, 2020 ), whereas the QTL cluster of 6AS.3 in this study colocalized with a QTL for parameters ST and SV reported by Guo et al (2020) . On the contrary, the other four QTL clusters of 1DS.1, 4AL.2, 4DS, and 7DS were not reported in previous studies, which were probable novel QTL clusters regulating the characteristics of gluten aggregation.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The QTL cluster of 3AS.1 colocalized with a detected QTL regulating grain protein content under late sowing time (LGPC) and wet gluten content under late sowing time (LWGC) reported by Lou et al (2020) . The QTL cluster of 3AL in this study overlapped with a detected QTL for LWGC and grain starch content under normal sowing time ( Lou et al, 2020 ), whereas the QTL cluster of 6AS.3 in this study colocalized with a QTL for parameters ST and SV reported by Guo et al (2020) . On the contrary, the other four QTL clusters of 1DS.1, 4AL.2, 4DS, and 7DS were not reported in previous studies, which were probable novel QTL clusters regulating the characteristics of gluten aggregation.…”
Section: Discussionmentioning
confidence: 51%
“…By comparing the QTL mapping results with QTLs reported in previous studies, we found that several QTLs were commonly detected in this study and previous studies ( Table 3 ). The QTL cluster of 1DL.2 overlapped with a detected QTL for parameters Mixolab protein weakening torque (C2), Mixolab development time (DT), Mixograph midline peak time (MPT), Mixograph midline peak value (MPV), Mixograph midline 8 min band width (MTxW), and Mixolab stability time (ST) reported by Jin et al (2016) , which also overlapped with a detected QTL for parameters dough development time of Farinograph, dough stabilization time of Farinograph and sedimentation volume reported by Guo et al (2020) . The QTL cluster of 3AS.1 colocalized with a detected QTL regulating grain protein content under late sowing time (LGPC) and wet gluten content under late sowing time (LWGC) reported by Lou et al (2020) .…”
Section: Discussionmentioning
confidence: 69%
“…A threshold P value of 0.001 (−log10(P) ≥ 3.0) was used for QTL detection, P value frequently used for many agronomical important quantitative traits [56][57][58]; suggestive QTL were considered at the sub-threshold 2.5 < −log10(P) < 3.0 when declared at least in one year. A QTL was considered stable when detected at −log10(P) ≥ 3.0 in at least two years [41,[58][59][60]. The phenotypic variation (PVE = R 2 ) and additive effect were estimated for each detected QTL.…”
Section: Statistical Analysis and Qtl Detectionmentioning
confidence: 99%
“…Among cereals, rice and wheat are also sources of protein in daily diets, though in limited quantity. The major effect of QTLs for grain protein content has been mapped in rice ( 28 , 33 , 39 , 43 ) and Wheat ( 15 , 17 , 22 ) ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%